(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
This passage explores how female characters in Shakespeare’s tragedies have been examined through feminist and psychoanalytic criticism. It highlights how feminist criticism sheds light on the restrictive gender roles imposed on characters like Ophelia, Desdemona, and Cordelia, while also recognizing figures like Lady Macbeth, Goneril, and Regan who challenge patriarchal norms. Psychoanalytic criticism investigates the unconscious motivations and internal psychological conflicts of female characters, using theories from Freud, Lacan, and Kristeva. The analysis focuses on characters’ desires, identity crises, and repressed emotions, revealing how these aspects influence their tragic ends. Together, these approaches present a multidimensional understanding of the psychological and social realities faced by Shakespeare’s women.